Cutting the costs of coastal protection by integrating vegetation in flood defences - Vincent T. M. van Zelst (Nature Portfolio, 2021)
Nearly one-third of the global coastline is vegetated. Incorporating these vegetation belts in coastal protection strategies would result in more sustainable and financially-attractive designs to mitigate the impacts of extreme coastal storms.